6th AIAA Atmospheric and Space Environments Conference 2014
DOI: 10.2514/6.2014-2060
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of a Hybrid Ice Protection System

Abstract: A key design factor impacting the utilization of electrical power to drive aircraft systems and subsystems is energy efficiency. With the design of an all-electric, hybrid ice protection system, energy consumption can be reduced to a large extent. The hybridization is achieved through an intentional partitioning of the ice at the stagnation line by melting via surface heating and ice shedding in the unheated regions of the airfoil surface via an electromechanical deicing system based on piezoelectric multilaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Finally, we have known that the electrical load required by the flight control system in period s P 3 ðsÞ is K leak ⋅ ðL e ðsÞ/A e Þ 2 /ρ hy where K leak is the leak coefficient addressing the relationship between the air-dynamical force on elevators and required hydraulic oil mass flow rate [29]. ρ hy is the density of the elevators' hydraulic oil and A e is the area of the elevators (4) The fourth kind of the increased loads for the MEA is the electrical warming of the leading-edge wings and elevators for ice protection [30,31]. The icing, which is usually caused by the supercooled water droplets in clouds where the aircraft is passing by, has been recognized as a potentially dangerous phenomenon for aircraft's flight, since the buildup of ice on the leading edges of wings/elevators can cause an irregular change of the aircraft's maneuverability characteristics and may finally result in the aircraft's loss of control [30].…”
Section: International Journal Of Aerospace Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we have known that the electrical load required by the flight control system in period s P 3 ðsÞ is K leak ⋅ ðL e ðsÞ/A e Þ 2 /ρ hy where K leak is the leak coefficient addressing the relationship between the air-dynamical force on elevators and required hydraulic oil mass flow rate [29]. ρ hy is the density of the elevators' hydraulic oil and A e is the area of the elevators (4) The fourth kind of the increased loads for the MEA is the electrical warming of the leading-edge wings and elevators for ice protection [30,31]. The icing, which is usually caused by the supercooled water droplets in clouds where the aircraft is passing by, has been recognized as a potentially dangerous phenomenon for aircraft's flight, since the buildup of ice on the leading edges of wings/elevators can cause an irregular change of the aircraft's maneuverability characteristics and may finally result in the aircraft's loss of control [30].…”
Section: International Journal Of Aerospace Engineeringmentioning
confidence: 99%
“…Since the above two kinds of costs are only corresponding to the variable x based on (25), the objective function can be stated as the linear expression in (30). The linear constraints in (31), involving only the variable x, contain the constraints which are stated by (3), (13), (14), (26), and (27). The nonlinear constraints in (32), which represent part of the constraints stipulating the stable operation for the engine and ECS while corresponding only to the variables x, include (12) and (28).…”
Section: The Proposed Solution Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming for applications as icephobic coatings in aircraft, a single hydrophobic coating to prevent or delay ice formation is not likely to be accepted considering strict safety reasons in the aerospace industry. An integration between the electro-thermal de-icing system with the icephobic coatings will have a better chance to be used in aircraft for reduction of energy consumption during electro-thermal heating to remove ice [42,43]. Therefore, an electrothermal heating test rig was applied to evaluate the energy consumption during heating until the ice block detached from the surface of the samples.…”
Section: Energy Consumption In the De-icing Testmentioning
confidence: 99%
“…However, the power consumption values are very high for the most common ice protection systems which are thermal. It was reported that consumed power density can reach up to 62 kW/m 2 for electro-resistive anti-/de-icing system [7]. Hot air systems, lead to a loss of power (thrust) from 10 to 15% for a turboprop engine [8].…”
Section: Introductionmentioning
confidence: 99%